Multi-Way Fluorescence Technique Combined with Four-Way Calibration for the Determination of Thiabendazole and Carbaryl in Apple - Haiyan Chang; Hailong Wu; Tong Wang; Xiaozhi Wang; Ruqin Yu (Chemosensors)
In this study, an excitation–emission–pH multi-way fluorescence technique coupled with a third-order calibration method based on an alternating quadrilinear decomposition (AQLD) algorithm was proposed for the simultaneous determination of thiabendazole (TBZ) and carbaryl (CAR) in apples. AQLD can be considered a “mathematical separation” technique that extracts the pure signal of the target analyte from complex mixed signals, thereby effectively addressing fluorescence peak overlap and unknown interference. The average spiked recoveries of the target analytes ranged from 98.4% to 101.9%, and the relative standard deviation was less than 5.6%. To evaluate the performance of the method, a number of parameters were calculated, including sensitivity (SEN), selectivity (SEL), limit of detection (LOD), limit of quantification (LOQ), and intra-day and inter-day precision. The results of the third-order calibration method were compared with those of the second-order calibration method (based on excitation–emission matrix fluorescence). These results showed that the former was superior. In short, the proposed strategy is simple, cost-effective, and anti-interference, providing a valuable reference for accurate quantification of TBZ and CAR in complex food matrices with uncalibrated interferences.